Mating behaviour, mate choice and female resistance in the bean flower thrips (Megalurothrips sjostedti) - Akinyemi, Adeyemi O. (Sci Rep, 2021)
Many species of thrips (Thysanoptera) in the family Thripidae form mating aggregations, but the adaptive significance of these aggregations and the extent of male and female mate choice is poorly understood. We studied the mating behaviour of the bean flower thrips Megalurothrips sjostedti (Trybom) (Thysanoptera: Thripidae), which forms male aggregations and occurs across sub-Saharan Africa. We tested whether males choose mates by female age or mating status. No-choice mating bioassays with one male and one female were used to simulate the way males usually encounter only one female at a time in aggregations in the field. Virgin females violently resisted mating attempts by males, but we found no compelling evidence to establish whether this was indiscriminate or was screening suitable males. Younger males (1–2 days old) did not discriminate females by age (1–2 or 7–10 days old), but older males (7–10 days old) avoided mating with older females. Any male choice by female mating status (virgin or mated) was weak or absent. The mating behaviour of M. sjostedti shows broad similarities with that of other thrips species that form aggregations, but also shows some distinct and novel differences, which can help our understanding of the adaptive significance of aggregations.